2022
DOI: 10.1177/11786469211066285
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Non-Purified and Semi-Purified Standard Diets on Kynurenine and Peripheral Metabolites in Male C57BL/6J Mice

Abstract: The kynurenine (Kyn) pathway plays crucial roles in several inflammation-induced disorders such as depression. In this study, we measured Kyn and other related molecules in the blood plasma, brain, and urine of male C57BL/6J mice (B6) fed non-purified (MF) and semi-purified (AIN-93G and AIN-93M) standard rodent diets. Mice fed MF had increased plasma Kyn levels compared with those on AIN93-based diets, as well as decreased hippocampal Kyn levels compared with those fed AIN-93G. Previous studies showed that bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…The rise of nutrition-related diseases such as diabetes mellitus, obesity, hypertension, and their comorbidities has created the need for animal research on treatment interventions and disease mechanisms. Mice are widely used as animal models in biomedical research, and manipulation of diet is the most effective way of regulating their health status, growth rate, reproduction, and survival rates [ 12 , 15 ]. We found that animals fed on either CBD or AIN-93M had similar weight.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rise of nutrition-related diseases such as diabetes mellitus, obesity, hypertension, and their comorbidities has created the need for animal research on treatment interventions and disease mechanisms. Mice are widely used as animal models in biomedical research, and manipulation of diet is the most effective way of regulating their health status, growth rate, reproduction, and survival rates [ 12 , 15 ]. We found that animals fed on either CBD or AIN-93M had similar weight.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, purified animal diets are composed of refined ingredients which serve as a source of a single nutrient, for example, isolated proteins such as casein, corn starch, sucrose, maltodextrin, soybean oil, purified vitamins, and minerals [ 11 , 12 ]. Purified diets are well defined and have open formulas that have minimal variability from batch to batch [ 2 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation